# 1/3 plus 2/9 as a fraction

1/3+2/9 = 5/9

1/3 plus 2/9 is equal to 5/9 in fraction and 0.5556 in decimal form.

1/3 + 2/9 = (?)

1/3 + 2/9 = [(1 x 9) + (2 x 3)]/(3 x 9)

= (9 + 6)/27

= 15/27

= (3 x 5)/(3 x 9)

= 5/9

1/3 + 2/9 = 5/9

1/3 plus 2/9 is equal to

1/3 is a fraction as an addend,

2/9 is a fraction as an addend,

5/9 is the sum of 1/3 and 2/9.

1/3 + 2/9 = 5/9

5/9 = 0.5556

1/3+2/9 as a decimal is 0.5556

0.5556 is the sum of 1/3 and 2/9.

1/3 plus 2/9 is equal to 5/9 in fraction and 0.5556 in decimal form.

**1/3+2/9 equals to**1/3 + 2/9 = (?)

1/3 + 2/9 = [(1 x 9) + (2 x 3)]/(3 x 9)

= (9 + 6)/27

= 15/27

= (3 x 5)/(3 x 9)

= 5/9

1/3 + 2/9 = 5/9

1/3 plus 2/9 is equal to

**5/9**__where__1/3 is a fraction as an addend,

2/9 is a fraction as an addend,

5/9 is the sum of 1/3 and 2/9.

**1/3 plus 2/9 as a decimal**1/3 + 2/9 = 5/9

5/9 = 0.5556

1/3+2/9 as a decimal is 0.5556

__where__0.5556 is the sum of 1/3 and 2/9.